Disposable paper-based PET fluorescence probe linked with calix[4]arene for lithium and phosphate ion detection. (25th October 2022) - Soni, Heni; Prasad, Jyoti; Pandya, Alok; Soni, Saurabh S.; Sutariya, Pinkesh G.
Abstract : As a part of our ongoing research, we have synthesized a new fluorescence probe, p-C4A, based on a calix[4]arene substituted with 4-aminoquinoline moieties with amide linkages for lithium and phosphate ions. Abstract : As a part of our ongoing research, we have synthesized a new fluorescence probe, p-C4A, based on a calix[4]arene substituted with 4-aminoquinoline moieties with amide linkages. p-C4A can selectively recognize Li + and PO4 3− ions and has been characterized via an emission study, an absorption study, ESI-MS spectroscopy, a 1 H NMR study and cyclic voltammetry. The fluorescence sensor p-C4A can operate over a concentration range of 5–170 nM for Li + sensing and 5–80 nM for PO4 3− sensing. The R 2 values obtained for the sensing of Li + and PO4 3− ions are 0.9962 and 0.9911, respectively. p-C4A demonstrates a minimum detection limit of 6.15 nM for Li + and 9.0 nM for PO4 3− . The quantum yields of p-C4A as its Li + and PO4 3− ion complexes were found to be 0.014 and 0.27, respectively. Herein, we report an easy-to-use, low-cost, disposable, paper-based, fluorescent, wax-printed device for the rapid chemical screening of Li + and PO4 3− . This device can be used as a quick, portable, multiple-test panel that is simple, lightweight, and disposable. Moreover, in order to assess its analytical applicability, the prepared sensor was successfully used for the determination of Li + and PO4 3− from wastewater samples, validating the proposed ion recovery method with 96–99% recovery rates.